Educating "Good Citizenship" through Bilingual Children Literature Arabic and Hebrew - Sara Zamir; Lea Baratz (Journal of Education and Learning (EduLearn), 2013)
The aim of the research has been to evaluate the contribution of the genre of bilingual literature, Arabic and Hebrew, to citizenship education. Since the Israeli society is a multicultural society comprised of both nations, Arabs and Jews who live in conflicted environment, one must regard those textbooks as civic agents. Literature is a socialization agent and as such it is an active influential factor in children's mental environment. The responsible citizens act responsibly in their community. They obey rules and regulation, acts kindly to his surroundings and occasionally donates out of their own resources. The participatory citizen actually participates in the social life of the community, at local, state and national levels by joining established systems. The justice citizen calls for attention to matters of injustice and to the importance of pursuing social goals. The content analysis procedure, revealed that most the  stories, hence, ten out the  thirteen  deal  with the  two elevated types  of citizenship,  namely,  the participatory citizen and the justice citizen.  Inspire  of  the  fact   that  we  are  dealing with  children's literature, the  authors  of  bilingual  children literature do not belittle the capacity of  children to  grasp  their role  as citizens in multicultural  society.